Ortotanásia e o direito à vida digna - Santo, André Mendes Espírito (2009)
This dissertation aims at studyi ng ortotanasia according to the constitutional principles of the right to life and dignity of the human being, with the intent to reflect on life concept and try to show that the life protected by the 1988 Constitution is not any life, but a worthy life. The text presents a reflection on the right to freedom and the bioethical principle of autonomy and the influence that such rights exercise over terminal patients. Further, it is discussed the theory of Ronald Dworkin with regard to the interaction of principles, rules and values and the relation that these three aspects have in the search for answers and solutions for apparent conflicts among constitutional principles. Furthermore, the different classifications about euthanasia as well as the convergences and differences with regard to ortotanasia are intended to be shown. Recent normative texts below the Constitution are also under analysis, especially No. 1.085/2006 of t he Medicine Federal Council which expressly determined the author ization from the physician to restrict or suspend procedures and treatments extending the life of the terminal patient with a serious and incurable disease, subject to the will of the person or his/her legal representative. The concern in this dissertation is to present the debate arisen amidst the legal and medical communities, with an opinion on the constitutionality of the Resolution and the ortotanasia. Finally, some actual cases of termi nal patients in other countries and in Brazil are presented so as to be analyzed, on the one hand, what is the treatment given to the subject in foreign law, and on the other hand, which has been the conduct adopted by Brazilian physi cians and patients when faced with the imminent end of life